2013
DOI: 10.1021/bc400365a
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Structure Determinants for Cation-Independent Mannose 6-Phosphate Receptor Binding and Cellular Uptake of a Recombinant Protein

Abstract: The cation-independent mannose 6-phosphate receptor (CI-MPR) plays a critical role in intracellular transport of lysosomal enzymes as well as the uptake of recombinant proteins. To define the minimal glycan structure determinants necessary for receptor binding and cellular uptake, we synthesized a series of glycans containing mono-, di-, tri-, tetra-, and hexamannoses terminated with either one or two phosphates for conjugating to a model protein, recombinant human acid α-glucosidase. A high affinity interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Design of a manufacturing process allowing for precise regulation of protein N -glycosylation is highly advantageous and urgently needed, as N -glycosylation often profoundly affects biological efficacy and pharmacokinetic properties of the manufactured drug substance [ 4 , 5 , 6 , 7 ]. Indeed, numerous preclinical studies have supported the strong relationship between the glycosylation structure decorating therapeutic proteins and their clinical properties, including protein stability, solubility, circulatory half-life, and efficacy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A well-characterized example of an N -glycosylation pattern affecting therapeutic efficacy was shown with the removal of the α-1,6-fucose residue attached to the innermost N -acetylglucosamine (GlcNAc) of the N -glycosylation core present on some anticancer antibodies such as rituximab and trastuzumab.…”
Section: Introductionmentioning
confidence: 99%
“…Design of a manufacturing process allowing for precise regulation of protein N -glycosylation is highly advantageous and urgently needed, as N -glycosylation often profoundly affects biological efficacy and pharmacokinetic properties of the manufactured drug substance [ 4 , 5 , 6 , 7 ]. Indeed, numerous preclinical studies have supported the strong relationship between the glycosylation structure decorating therapeutic proteins and their clinical properties, including protein stability, solubility, circulatory half-life, and efficacy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A well-characterized example of an N -glycosylation pattern affecting therapeutic efficacy was shown with the removal of the α-1,6-fucose residue attached to the innermost N -acetylglucosamine (GlcNAc) of the N -glycosylation core present on some anticancer antibodies such as rituximab and trastuzumab.…”
Section: Introductionmentioning
confidence: 99%
“…714 For example, conjugation of synthetic M6P oligosaccharides to the recombinant human acid α -glucosidase (rhGAA) through selectively oxidized sialic acid or galactose residues in the N -glycans of the enzyme led to M6P-modified rhGAA that showed an enhanced uptake and demonstrated up to 5-fold greater potency than the unmodified rhGAA in a Pompe disease mouse model. 911 Despite these promising studies, chemical conjugation suffers from heterogeneity in linkage sites, potential instability of the conjugates, and introduction of unnatural linkers that may be immunogenic in humans. Moreover, as to the molecular recognition between CI-MPR receptor and M6P-glycoproteins, it is still not fully understood how the location of the M6P moiety in the oligosaccharide, the valency of the M6P ligands, and/or the oligosaccharide context affect the binding and affinity for the M6P receptor CI-MPR.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the unsuccessful targeting of HP-GAA, a series of approaches employing chemical conjugation of M-6-P glycans have been shown to improve the clearance of accumulated glycogen in the skeletal muscles of Pompe mice as well as MPR binding and subsequent targeting to lysosomes (28 - 32) . In a proof-of-concept study, Genzyme researchers isolated M-6-P glycans from recombinant GLA (Agalsidase beta) and, after derivatization to glycosylhdrazines, attached these M-6-P glycan to periodate-oxidized sialic acids of GAA using carbonyl chemistry (28) .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials examining the safety and efficacy of this GAA are currently underway (33) . Recently, glycan structures for efficient CI-MPR binding were determined using the chemical conjugation of various glycans containing phosphate groups (32) . Zhou et al , reported that the tightest binding to CI-MPR was achieved with a hexamnnose structure containing two phosphates, while the phosphorylated dimannose moiety appears to be the minimal structure for binding.…”
Section: Introductionmentioning
confidence: 99%